Time-resolved measurement of photocarrier generation in CH3NH3PbI3 single crystals. (May 2019) - Tanaka, Y; Akimoto, I
Abstract: A giant microwave response is transiently observed in CH3 NH3 PbI3 single crystals under pulsed laser excitation at temperatures in both structural phases across the transition at 161 K. The response is caused by photocarriers generated in the specimen mounted in a microwave cavity. This detection technique is capable of measuring the carrier dynamics with a time-resolution of a few nanoseconds. Based on the time-resolved excitation spectrum near the absorption edge, we unveil that the photocarriers are generated by long-lived excitons as well as by fast band-to-band transition.